Eine empirische Analyse von Sanktionen für Arbeitslose in Westdeutschland während der 1980er und 1990er Jahre - Ralf A. Wilke (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
– This paper is to provide a first insight into the sanction instrument of benefit suspension, existing in two forms, for people receiving benefits from the Federal Employment Service. The research is based on extensive individual datasets from the Federal Employment Service, the IAB employment sample, and examines the period 1980-1997. After 57% of all sanctions during the course of a period of benefit, the unemployed person concerned received a benefit from the Federal Employment Service again within six days, usually because the sanctions were withdrawn for important reasons. Only 41% of all sanctions imposed can actually be regarded as having the effect of a true sanction. As a result of these findings it is doubtful that an undifferentiated policy of activating the unemployed with an associated increase in the imposition of benefit suspension for various reasons has a totally positive effect, as the additional administrative work and expenditure resulting from the high rate of withdrawal of sanctions can not be covered by the expected utility in many cases.
Keywords: 330; Sperrzeit; Leistungsempfänger; IAB-Beschäftigtenstichprobe; Arbeitslose; Westdeutschland; Bundesrepublik Deutschland